Very late relapse of high-grade osteosarcoma: A case report and review of the literature. Issue 29 (17th July 2020) - Kaneuchi, Yoichi; Hakozaki, Michiyuki; Yamada, Hitoshi; Hasegawa, Osamu; Yamada, Shoki; Oka, Yuka; Watanabe, Kazuo; Konno, Shinichi
Abstract: Rationale: Osteosarcoma is the most common primary malignant bone tumor in children. The prognosis of osteosarcoma has improved with the use of aggressive systemic chemotherapy in addition to surgery. The relapse of osteosarcomas is usually as lung metastasis observed within 2 to 3 years after the initial treatment. A relapse is rarely observed at >10 years. Patient concerns: We report the case of a 51-year-old Japanese man who was treated for high-grade osteosarcoma of the femur at 13 years old. He was referred to our hospital with a suspicion of primary lung cancer based on back pain, respiratory distress, and an abnormal mass on chest radiograph. Diagnoses: Computed tomography-guided biopsy confirmed the lung lesion as a metastatic recurrence of high-grade osteosarcoma without local recurrence. Interventions: Chemotherapy was planned, but the patient's general condition rapidly deteriorated and thus palliative therapy was provided. Outcomes: The patient died 2 months after the initial consultation. Lessons: The survival durations of osteosarcoma patients have been prolonged by recent progress in multimodality therapy, and thus clinicians as well as osteosarcoma patients should always keep in mind the possibility of very late relapse.